Climatic Teleconnections and Fire Hotspot Seasonality in Bolivia (2000–2025): Association with Niño 3.4, PDO, and SAM Indices - Torrez, Guillermina Miranda (European Journal of Applied Sciences, 2026)
The occurrence of fire hotspots in Bolivia results from a complex interaction between regional climatic seasonality and large-scale ocean–atmosphere variability. The objective of this study was to analyze the relationship between global climate indices and the monthly dynamics of fire hotspots across four Bolivian biomes during the period 2000–2025. This was achieved through time-series analysis, the calculation of the Seasonal Variation Index (SVI), and the evaluation of monthly variability in local meteorological variables. A quantitative, observational, longitudinal, and retrospective approach was adopted, based on monthly series of fire hotspots, maximum temperature, minimum relative humidity, and maximum wind speed from the meteorological stations of El Alto, Cochabamba, Viru Viru, and San José de Chiquitos. Temporal characterization included descriptive statistics, Sen’s slope estimator, autocorrelation functions, and the Ljung–Box test, while intra-annual seasonality was examined using the SVI. Furthermore, associations between the Niño 3.4 index, the Pacific Decadal Oscillation (PDO), and the Southern Annular Mode (SAM) with local meteorological variables were estimated using Pearson correlations with lags ranging from 0 to 5 months. The results revealed a non-random temporal structure dominated by a persistent annual periodicity and, in several cases, a secondary biennial signal. The SVI indicated that fire hotspot activity was seasonally concentrated between August and October, with a principal peak in September, coinciding with positive anomalies in maximum temperature and negative anomalies in minimum relative humidity. In the association analysis, the Niño 3.4 index exhibited the strongest positive correlations with maximum temperature, particularly in Cochabamba, whereas the SAM displayed the clearest inverse signal with minimum relative humidity in El Alto. The PDO showed weaker and more heterogeneous associations. It is concluded that the monthly dynamics of fire hotspots in Bolivia are strongly structured by climatic seasonality, and that local meteorological variability exhibits differential associations with global climate forcings. This provides an analytical foundation useful for seasonal monitoring and wildfire risk management.